Chemical reactions of atomic lithium and molecular calcium monohydride at 1 K - Singh, V.; Hardman, K.; Tariq, N.; Lu, M.; Ellis, Aja; Morrison, M.; Weinstein, J. (The American Physical Society, 2012)
Using cryogenic helium buffer-gas cooling, we have prepared dense samples of atomic lithium and molecular calcium monohydride at temperatures as low as 1 K. We have measured the Li+CaH→LiH+Ca chemical reaction, observed in both the accelerated disappearance of CaH in the presence of high densities of lithium and in the appearance of the LiH molecule.